Konsep Kristologi Konsili Kalsedon Dalam Menanggapi Ajaran Eutyches Pada Tahun 451 Dan Integrasinya Dalam Pendidikan Agama Kristen - Gultom, Mangarimbun; Simanjuntak, Candra Gunawan Marisi (Sekolah Tinggi Teologi Real Batam, 2024)
The year 451 became an important event in the history of the church when it formulated a creed through a council aimed at responding to the teachings of Eutyches, which eventually became a firm hold as the formulation of the correct teaching on Christology in the church. This age also has the same challenge with the birth of Christology teachings that are different from the Bible such as the Judahite witness and other unsubstantiated teachings in social media. That is why this paper is important because it aims to provide a contribution of knowledge for the PAK of this age, which provides a concept of Christology as a foundation for the correct teaching of Christology. This research uses a qualitative method with a descriptive approach, where the author uses various sources of existing literature to obtain comprehensive study results. The main statement of the Council of Chalcedon was to affirm the doctrine known as “Chalcedonian Christology”, which states that Jesus is truly God and truly man, and both natures are present in Him simultaneously. Eventually, a concept of Christology emerged in which Christ is “recognized in two unmixed, unchanging, undivided, inseparable natures. Keywords: council of chalcedon; eutychianism; christology; christian education The year 451 became an important event in the history of the church when it formulated a creed through a council aimed at responding to the teachings of Eutyches, which eventually became a firm hold as the formulation of the correct teaching on Christology in the church. This age also has the same challenge with the birth of Christology teachings that are different from the Bible such as the Judahite witness and other unsubstantiated teachings in social media. That is why this paper is important because it aims to provide a contribution of knowledge for the PAK of this age, which provides a concept of Christology as a foundation for the correct teaching of Christology. This research uses a qualitative method with a descriptive approach, where the author uses various sources of existing literature to obtain comprehensive study results. The main statement of the Council of Chalcedon was to affirm the doctrine known as “Chalcedonian Christology”, which states that Jesus is truly God and truly man, and both natures are present in Him simultaneously. Eventually, a concept of Christology emerged in which Christ is “recognized in two unmixed, unchanging, undivided, inseparable natures. Keywords: council of chalcedon; eutychianism; christology; christian education AbstrakTahun 451 menjadi suatu peristiwa penting dalam sejarah gereja ketika merumuskan suatu kredo melalui suatu konsili yang bertujuan untuk menanggapi ajaran Eutyches, yang akhirnya menjadi pegangan teguh sebagai rumusan ajaran yang benar tentang Kristologi di dalam gereja. Zaman ini pun juga memiliki tantangan yang sama dengan lahirnya ajaran Kristologi yang berbeda dengan Alkitab seperti saksi Yehuda dan pengajaran lainnya yang tidak berdasar di dalam sosial media. Itu sebabnya tulisan ini menjadi penting karena bertujuan untuk memberikan suatu sumbangan ilmu bagi PAK zaman ini, yang memberikan suatu konsep kristologi sebagai pondasi pengajaran yang benar tentang Kristologi. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, dimana penulis menggunakan berbagai sumber litertur yang ada untuk mendapatkan hasil kajian yang komprehensif. Pernyataan utama dari Konsili Kalsedon adalah menegaskan doktrin yang dikenal sebagai “Kristologi Kalsedon”, yang menyatakan bahwa Yesus adalah benar-benar Allah dan benar-benar manusia, dan kedua natur tersebut hadir dalam diri-Nya secara bersamaan. Akhirnya muncul suatu konsep Kristologi yang berisikan Kristus diakui di dalam dua Hakikat yang tidak bercampur, tidak berubah, tidak terbagi, tidak terpisah.Kata Kunci: konsili kalsedon; eutykhianisme; kristologi; pak